Metacognitive, Critical Thinking, and Concept Understanding of Motion Systems: A Correlational Study - Az-Zahra, Rania; Rusdi, Rusdi; Ristanto, Rizhal Hendi (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
Metacognition skills (MS) is an individual's ability to evaluate and regulate his own thinking. Critical thinking skills (CTS) is the ability to apply the knowledge to solve problems, evaluate information, and make solutions. Conceptual understanding (CU) refers to an integrated and functional understanding of scientific knowledge. This study aims to analyze the correlation between MS and CU on motion system; CTS and CU; and MS and CTS. This research was conducted at Public High School (PHS) 3 Bekasi in February – March 2021 by involving a sample of 110 students of Grade 11 Mathematics and Science Class, who were selected through simple random sampling technique. The instrument used were the essay test, and a multiple-choice test distributed online. The research method is descriptive method with correlational studies. The results show that there is a positive relationship between MS and CU on Motion System with a correlation of 0.967; CTS and CU with a correlation of 0.431; and MS and CTS with a correlation of 0.978.